A natural history of dragons : a handbook for students by Anastasia Vladislav - Hawkins, Emily (Frances Lincoln Children's Books, 2024)
"Stories about majestic, fire-breathing creatures have been told for centuries. . . but are they merely legends, or is there any truth to these age-old tales? Delve into this recently discovered handbook for students of the Academie Solomonar: the only school for dragon-riders. This detailed volume, written by dragon expert Anastasia Vladislav, reveals knowledge once known only by students of this exclusive school. You will meet dragons from around the world, find out about their habits and habitats, learn the science of how they breathe fire, and explore the mysteries of dragon flight. Prepare to discover a hidden world that will delight fantasy enthusiasts of all ages."--Page 4 of cover.